2016
DOI: 10.1021/acs.energyfuels.6b01524
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Negative Electrospray Ionization and Positive Atmospheric Pressure Photoionization Fourier Transform Ion Cyclotron Resonance Mass Spectrometry as a Quantitative Approach of Acid Species in Crude Oils

Abstract: Crude oils differ from one another in numerous chemical and physical properties, many of which play an important role in defining their quality and price. Generally, statistical analysis of price differentials has focused on two main properties: density and sulfur content. However, the growing significance of high total acid number (TAN) crude oils, especially from developing countries, has aroused the necessity for extending these models. Consequently, refineries must obtain real and exact information regardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 29 publications
(55 reference statements)
0
25
0
Order By: Relevance
“…32 In agreement with our results, the same optimal accumulated scans have also been reported. 15,32,33 Some studies have, however, applied twice as high accumulated scans, 200, but we found that accumulated scans above 100 results in MS with similar quality. 34,35 Some studies have described the use of sheath, auxiliary and sweep gases in crude oil analysis by APPI(±)-MS, but the values cannot be found in the manuscripts.…”
Section: Full Factorial Designmentioning
confidence: 71%
See 2 more Smart Citations
“…32 In agreement with our results, the same optimal accumulated scans have also been reported. 15,32,33 Some studies have, however, applied twice as high accumulated scans, 200, but we found that accumulated scans above 100 results in MS with similar quality. 34,35 Some studies have described the use of sheath, auxiliary and sweep gases in crude oil analysis by APPI(±)-MS, but the values cannot be found in the manuscripts.…”
Section: Full Factorial Designmentioning
confidence: 71%
“…34,35 Some studies have described the use of sheath, auxiliary and sweep gases in crude oil analysis by APPI(±)-MS, but the values cannot be found in the manuscripts. 15,31,32…”
Section: Full Factorial Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The need to characterize NAs is driven by environmental and crude oil processing reasons because, despite their low abundance in crude oils, NAs are the main corrosive species in acidic crude oils. , Additionally, NAs are the major contributor to the total acid number of a crude oil. A high total acid number reduces the value of a crude oil because this causes corrosion and other refinery problems. , Thermal degradation of crude oil has been reported to reduce its total acid number because this process can decarboxylate NAs . It is possible that decarboxylation of NAs can be improved if NAs are better characterized.…”
Section: Applicationsmentioning
confidence: 99%
“…A high total acid number reduces the value of a crude oil because this causes corrosion and other refinery problems. 118,119 Thermal degradation of crude oil has been reported to reduce its total acid number because this process can decarboxylate NAs. 120 It is possible that decarboxylation of NAs can be improved if NAs are better characterized.…”
Section: Sophisticated Instrumentation Requiredmentioning
confidence: 99%